Potentially Competitiveness of Cassava Commodity in Internasional Trade:A Case of Central Sulawesi Economy - Yulianti kalaba; Sisfah Yuni; Dafina Howara; Abdul Muis; Marwan Yantu (AGROLAND The Agricultural Sciences Journal (e-Journal), 2014)
Cassava commodity has strong linkages with other industries. This is indicated by coefficient of its multiplier effect being greater than one. That means that investment of IDR 1 billion for the commodity will affect total economic activity of Central Sulawesi as big as the coefficient. The aim of this study is to estimate potentially competitiveness of cassava commodity of Central Sulawesi in international trade. In particular, the aim of this study is to estimate (i) potentially competitive advantage of cassava commodity; (ii) potentially comparative advantage of cassava commodity; (iii) level of governmental protection to price of tradable input for cassava; (iv) level of governmental protection to cassava outputs; and (v) level of simultaneously protection to cassava output sand tradable inputs for cassava. PAM method was used by using time series data of during 2000 – 2013 from BPS and FAO. The results of analysis shows that cassava commodity from Central Sulawesi has potentially competitiveness in international trade. This is showed by (i) potentially competitive advantage was indicated by PCR is less than one; thus cassava farm can be developed on a large scale; (ii) potentially comparative advantage was indicated by DRC is less than one; This means that in developing for cassava farm can be done by saving the resources; (iii) NPCR is equal to zero to show that government policies to tradable inputs is very protective, but actually that was caused by farmers didn’t apply fertilizers and pesticides; thus developing for cassava farm can be done by organic farm, so cassava farm can be became as entry point in green economy of Central Sulawesi; (iv) NPCO is less than one meaning that government policies for output prices is in-protective, so cassava farmers didn’t enjoy actual prices of cassava output; and (v) EPC is less than one meaning that beside government policies for prices of cassava output is in-protective, government policies for tradable inputs is also in-protective; thus although the farmers didn’t enjoy the surplus prices, however they can pay tradable inputs being lower than actual prices of the tradable inputs.